KOMUNIKASI SEBAGAI INTERVENING VARIABEL PENGARUH KARAKTERISTIK INDIVIDU TERHADAP KINERJA PEGAWAI - Sudung Simatupang (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2019)
Human resources are also the key that determines organizational development. Employee performance is very important to be considered by every organization, because the performance of employees with all aspects in it will have an overall impact on the development of the organization. The purpose of this study is to determine communication as an intervening variable influence individual characteristics on employee performance. Sample used by all civil servants (PNS) at UPT SDA Bah Bolon, Dinas Sumber Daya Air, Cipta Karya, dan Tata Ruang Provinsi Sumatera Utara Jl. Asahan Km. 3,5 Pematangsiantar which numbered 96 employees. The analysis technique used is simple regression and multiple regression. The results of the study found results: (1). There was a signi ﬁ cant effect of individual character on communication: (2). There is a significant influence of individual character and communication on performance: (3). For the results of intervening path analysis shows that individual characters can have a direct effect on employee performance and can also indirectly influence from individual character to communication (as intervening) and then towards employee performance. The results of the above analysis show that indirectly the individual character through communication has a significant influence on performance